HUBUNGAN FAKTOR PERSONAL (EMPATI) DENGAN PERILAKU ALTRUISTIK PADA ANGGOTA KORPS SUKARELA PALANG MERAH INDONESIA (KSR-PMI) DI INSTITUSI X: Correlation of Personal Factor (Empathy) with Altruistic Behaviour in Members of Volunteer Corps-Indonesian Red Cross(KSR-PMI) on Institution X (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2019)
The emergency is a condition when a person is in a life-threatening condition or even can cause permanent disability if not helped immediately. Therefore it is necessary to improve the quality of emergency services in an integrated between the Indonesia Cross Red and other sectors, especially the corps of volunteer, but most of the volunteer members do not want to participate in emergency first aid activities. The purpose of this research is to know the relationship between personal factors (Empathy) and altruistic behavior in the KSR PMI X members. The method in this study is correlative analytics with the cross-sectional approach. The population of this study was all members of the corps of volunteer-Indonesia cross red in institution X. The sample in this study was 63 research members, using consecutive sampling. Data collection using questionnaires that have passed the test of validity and reliability. Analysis of the data used was rank spearmen. The results showed rank spearman hypothesis test that the correlation coefficient of 0.492 (p = 0.001; p <0.05), showed a positive direction, and the strength of the relationship was moderate, while H1 was accepted there was a relationship between personal factors (empathy) and altruistic behavior. Therefore, it is expected that all KSR-PMI members can develop their empathy, increase their commitment to participating in emergency activities.